LncRNA-mediated ceRNA network reveals the mechanism of action of Saorilao-4 decoction against pulmonary fibrosis - Fu, Xinyue; Song, Xinni; Niu, Shufang; Shi, Songli; Chang, Hong; Qi, Jun; Wang, Peng; Bai, Wanfu (Frontiers in Genetics, 2024)
Pulmonary fibrosis (PF), a type of interstitial pneumonia with complex etiology and high mortality, is characterized by progressive scarring of the alveolar interstitium and myofibroblastic lesions. In this study, we screened for potential biomarkers in PF and clarified the role of the lncRNA-miRNA-mRNA ceRNA network in the inhibitory effect of SRL-4 on PF. Healthy male SPF SD rats were randomly divided into three groups, namely CON, MOD, and SRL-4. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses were performed to determine the biological functions of the target genes. A visualized lncRNA-miRNA-mRNA ceRNA network was constructed using Cytoscape, while key genes in the network were identified using the cytoNCA plugin. Seventy-four differentially expressed lncRNAs and 118 differentially expressed mRNAs were identified. Gene Ontology analysis revealed that the target genes were mainly enriched in the cell membrane and in response to organic substances, while Kyoto Encyclopedia of Genes and Genomes analysis showed that the target genes were mainly enriched in the AMPK, PPAR, and cAMP signaling pathways. We elucidated a ceRNA axis, namely Plcd3-OT1/rno-miR-150-3p/Fkbp5, with potential implications in PF. Key genes, such as AABR07051308.1-201, F2rl2-OT1, and LINC3337, may be important targets for the treatment of PF, while the AMPK, PPAR, and cAMP signaling pathways are potential key targets and important pathways through which SRL-4 mitigates PF. Our findings suggest that SRL-4 improves PF by regulating the lncRNA-miRNA-mRNA network.